25 years single market: Which trade and growth effects? - Fritz Breuss (Austrian Institute of Economic Research (WIFO), 2018)
The EU Single Market and the Maastricht Treaty are now aged 25. In this short history many events marked the way: the creation of EMU in 1999, the introduction of the euro in 2002, and the great EU enlargement starting in 2004. And lastly - for the first time - with the Brexit a reverse of the process of European integration takes place. The recession of 2009 and the Euro crisis in 2010 led to a setback in the economic development in the EU. A quarter of a century invites to look back about the achievements. How much trade and economic growth could be created by the Single Market plus euro plus EU enlargement? These questions are treated here with the help of a consistent integration model. Embedded into an endogenous growth model approach growth and trade effects for EU and EFTA countries are estimated. It turns out that (taking also into account GATT liberalisation) the European integration added to per-capita GDP 0.5 percentage point to EU 28 countries but only 0.2 percentage point to EFTA countries. Trade openness increased by 0.9 percentage point of GDP in EU 28 and by 0.3 percentage point in EFTA countries.
Keywords: C23; C51; F15; O52; 330; European Integration; Single Market; Maastricht Treaty; Model simulations